Plant hydraulics as a central hub integrating plant and ecosystem function: meeting report for ‘Emerging Frontiers in Plant Hydraulics’ (Washington, DC, May 2015) - Sack, Lawren; Ball, Marilyn C.; Brodersen, Craig; Davis, Stephen D.; Des Marais, David L.; Donovan, Lisa A.; Givnish, Thomas J.; Hacke, Uwe G.; Huxman, Travis; Jansen, Steven; Jacobsen, Anna L.; Johnson, Daniel M.; et al. (Plant, cell and environment, 2016)
Water plays a central role in plant biology and the efficiency of water transport throughout the plant affects both photosynthetic rate and growth, an influence that scales up deterministically to the productivity of terrestrial ecosystems. Moreover, hydraulic traits mediate the ways in which plants interact with their abiotic and biotic environment. At landscape to global scale, plant hydraulic traits are important in describing the function of ecological communities and ecosystems. Plant hydraulics is increasingly recognized as a central hub within a network by which plant biology is connected to palaeobiology, agronomy, climatology, forestry, community and ecosystem ecology and earth‐system science. Such grand challenges as anticipating and mitigating the impacts of climate change, and improving the security and sustainability of our food supply rely on our fundamental knowledge of how water behaves in the cells, tissues, organs, bodies and diverse communities of plants. A workshop, ‘Emerging Frontiers in Plant Hydraulics’ supported by the National Science Foundation, was held in Washington DC, 2015 to promote open discussion of new ideas, controversies regarding measurements and analyses, and especially, the potential for expansion of up‐scaled and down‐scaled inter‐disciplinary research, and the strengthening of connections between plant hydraulic research, allied fields and global modelling efforts. Plant hydraulics is increasingly recognized as a central hub relating fields within plant biology, ecology, evolution, palaeobiology and agriculture, essential to grand challenges such as anticipating and mitigating the impacts of climate change, and improving the security and sustainability of our food supply. A workshop entitled ‘Emerging Frontiers in Plant Hydraulics’ supported by the National Science Foundation, was held in Washington DC, 2015. We summarize the discussions, including controversies regarding measurements and analyses, the emerging frontiers of up‐scaled and down‐scaled inter‐disciplinary research, and the strengthening of connections between research in plant hydraulics, that in allied fields and global modelling efforts.